The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1248/bpb.33.122
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Flavonoid Glycosides Isolated from the Peel of Japanese Persimmon (Diospyros kaki 'Fuyu') on Melanin Biosynthesis

Abstract: We found that the acetone extract of the peel of Japanese persimmon (Diospyros kaki 'Fuyu') inhibits melanin biosynthesis in mouse B16 melanoma cells. The activity-guided purification of the extract resulted in isolation of two active compounds, which have been identified as flavonoid glycosides, isoquercitrin (quercetin-3-O-glucoside) and hyperin (quercetin-3-O-galactoside) by spectral analysis. Isoquercitrin and hyperin strongly inhibited the production of melanin (IC 50 : 21.7 and 18.2 m mM, respectively). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 12 publications
(7 reference statements)
0
27
0
Order By: Relevance
“…Recent reports have demonstrated that the extracts prepared from leaves, peels and flesh of persimmon have anti-tumour (Khanal, Oh, Thuong, Cho, & Choi, 2010), anti-hyperlipidemia (Lee, Cho, & Yokozawa, 2008a), anti-diabetes (Lee, Kim, Cho, & Yokozawa, 2007), anti-oxidant (Chen, Fan, Yue, Wu, & Li, 2008;Lee, Cho, & Yokozawa, 2008b), and neuroprotective activities (Bei et al, 2009). In our previous study, we isolated two distinct flavonoid glycosides from the peel of persimmon, which were shown to inhibit melanogenesis in B16 mouse melanoma cells (Ohguchi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports have demonstrated that the extracts prepared from leaves, peels and flesh of persimmon have anti-tumour (Khanal, Oh, Thuong, Cho, & Choi, 2010), anti-hyperlipidemia (Lee, Cho, & Yokozawa, 2008a), anti-diabetes (Lee, Kim, Cho, & Yokozawa, 2007), anti-oxidant (Chen, Fan, Yue, Wu, & Li, 2008;Lee, Cho, & Yokozawa, 2008b), and neuroprotective activities (Bei et al, 2009). In our previous study, we isolated two distinct flavonoid glycosides from the peel of persimmon, which were shown to inhibit melanogenesis in B16 mouse melanoma cells (Ohguchi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…3,[8][9][10] The peels of fresh astringent persimmons are usually removed and dried, which yields sweet dried persimmon peels. The peel was found to contain more polyphenols 11) and carotenoids 12) than the fruit body.…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7] With regard to its pharmacological activities, many studies have reported pharmacological effects including antioxidant activity and tyrosinase inhibitory activity. 3,[8][9][10] The peels of fresh astringent persimmons are usually removed and dried, which yields sweet dried persimmon peels. The peel was found to contain more polyphenols 11) and carotenoids 12) than the fruit body.…”
mentioning
confidence: 99%
“…The structures of isolated compounds were identified by a combination of spectroscopic methods (MS, 1 D NMR and 2D NMR) and comparisons with the literature data as a mixture of quercetin 3-β-Ogalactopyranoside or hyperoside (1) and quercetin 3-β-Oglucopyranoside or isoquercitrin (1:1) (2) (Almeida et al, 1998;Costa et al, 2007;Ohguchi et al, 2010), quercetin 3-O-α-rhamnoside or quercitrin (3) (Zhong et al, 1997), luteolin 6-C-β-glucopyranoside or orientin (4) (Li et al, 2009), apigenin-6-C-glucoside or isovitexin (5) (Leong et al, 2010), kaempferol 3-O-α-rhamnoside (6) (Fossen et al, 1999) and lupenone (7) (Prachayasittikul et al, 2010), respectively. Characterization of the sugar moieties from the mixture of quercetin 3-β-galactopyranoside (1) and quercetin 3-β-glucopyranoside (2) was performed according Cota et al 2008b.…”
Section: Resultsmentioning
confidence: 99%